Prevalence of common oral diseases among Senior Secondary School students in Enugu State, Nigeria - Okoli, Scholastica Chidi; Ogbalu, Anthony Ikechukwu; Ani, Samuel Emeka; Nwosu, Peter Chijioke; Enebechi, Paul Chima; Hussein , Balarabe Musa; Omale, Johnson John (Orapuh Journal, 2021)
Introduction General health could be affected by infections of the teeth and other tissues in the mouth leading to oral disease. Oral diseases include dental caries, periodontal diseases, oral cancer, clefts, dental stains, halitosis (mouth odour), gingivitis, tooth wear, pericoronitis, oral ulcers, oral candidiasis, cancrum oris, and others Purpose This study was aimed at ascertaining the prevalence of common oral diseases (COD) among senior secondary school students in Enugu State. Materials and Methods The descriptive survey design was adopted for the study. The population comprised of all the 50,736 senior secondary school students in government-owned secondary schools in Enugu State, Nigeria. The sample size for the study was 900 students. Four research questions and two hypotheses were posed for the study. A researcher-made questionnaire cum data collection form (PPCOD) was the instrument used for the study. The instrument was validated by three research experts and the reliability was tested using Kuder Richardson’s formula – 20 (K –R20) at a 0.05 level of significance and a reliability coefficient of 0.97 was derived. Frequencies, percentages, and chi-square statistics at a 0.05 level of significance were utilized for data analyses. Results The prevalence of COD was 30.6% for dental caries and 19.2% for periodontal disease. The gender-related prevalence of COD was higher among males (33.9% and 31.8%) than females (29% and 13.4%). The prevalence of COD increased with increase in age. The prevalence of COD was higher among students in the rural secondary schools (37.2% and 21.6%) than their urban counterparts (27.3% and 18%). There was no significant gender-difference in the prevalence of dental caries (p>0.05) but there was a significant gender-difference in the prevalence of periodontal diseases among the students (p<0.05). There were significant age-differences in the prevalence of dental caries and periodontal diseases (p<0.05). Conclusion Sensitization campaigns on common oral diseases needs to be carried in schools and communities. Also, oral health care professionals should be engaged to work on school oral health programmes.